Constructing two-dimensional heterojunction through decorating covalent organic framework with MoS2 for enhanced photoelectrochemical water oxidation. Issue 1 (February 2022) - Zhou, Zhiming; Li, Peize; Gao, Xiaowu; Chen, Jinjin; Akhtar, Kalsoom; Bakhsh, Esraa M.; Khan, Sher Bahadar; Shen, Yan; Wang, Mingkui
Abstract: Photoelectrochemical (PEC) water splitting is regarded as one of the most effective route to address energy crisis and environmental issues. Two-dimensional covalent organic frameworks (2D COFs) have made some advances in PEC water splitting owing to their functionalized building blocks, remarkable structural stability, and unique conjugated structures, etc. Unfortunately, the PEC performance of COFs is severely hindered because of the poor surface charge transfer, surface recombination at the photoanode/electrolyte junction, and sluggish oxygen evolution reaction (OER) kinetics. Herein, we report an efficient 2D heterojunction through decorating a 2D COF with MoS2 for enhanced PEC water oxidation. The photocurrent density and incident photon conversion efficiency (IPCE) of the resultant photoanode are effectively improved by constructing 2D COF-based heterojunction. Such a strategy of constructing 2D heterojunction can not only efficiently accelerate the charge separation and transfer but also promote the separation of photogenerated electron-hole pairs for oxygen evolution. This work provides rational suggestions for developing COF-based photocatalysts to address the energy crisis and various environmental issues. Graphical Abstract: An efficient two-dimensional (2D) heterojunction was successfully constructed through decorating a 2D covalent organic framework (COF) with MoS2 for photoelectrochemical (PEC) water oxidation. Its enhanced PEC performance can be attributed to the fast charge transfer and efficient separation of photogenerated carriers. ga1 Highlights: A two-dimensional (2D) heterojunction was fabricated by decorating a covalent organic framework (TTZ-COF) with MoS2 . The photoelectrochemical (PEC) performance of MoS2 /TTZ-COF was clearly enhanced. 2D heterojunction significantly accelerated the charge transfer and promoted the separation of photogenerated carriers. This work provided a rational strategy to design and fabricate COF-based photocatalysts for solar-driven water splitting.